2022
DOI: 10.1177/21582440221082127
|View full text |Cite
|
Sign up to set email alerts
|

Review of Organizational Ambidexterity Research

Abstract: The main objective of this research is to investigate how organizational ambidexterity can be achieved at a modern organization. A concise review of key studies conducted until today consolidates the state of academic research on the subject of organizational ambidexterity, as the ambidexterity concept has been gaining increased attention from scholars. The systematic search of the literature published since 1991, composed of 122 articles, has revealed various research perspectives with respect to organization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 166 publications
1
36
0
Order By: Relevance
“…Researchers have expressed contradictory views on OA and its impacts on FP in the literature (Kassotaki, 2022). Gibson and Birkinshaw (2004) found that obtaining ambidexterity through contextual support is possible, which positively correlated with FP (Gibson & Birkinshaw, 2004).…”
Section: Creating Research Hypothesesmentioning
confidence: 99%
“…Researchers have expressed contradictory views on OA and its impacts on FP in the literature (Kassotaki, 2022). Gibson and Birkinshaw (2004) found that obtaining ambidexterity through contextual support is possible, which positively correlated with FP (Gibson & Birkinshaw, 2004).…”
Section: Creating Research Hypothesesmentioning
confidence: 99%
“…Firms that mainly pursue exploitation achieve returns that are predictable but not necessarily sustainable; they may enhance their short-term performance, but that can result in a competence trap, as they may not be able to respond adequately to environmental changes. On the contrary, previous scholars have acknowledged that for firms to compete successfully in the long-term, they probably need to be able of pursing exploitation and exploration, with ambidexterity being a key driver in their long-term performance (Kassotaki, 2022). Therefore, firms must pursue an optimal mix of exploration and exploitation in order to remain competitive both in the short-and long-term (Gibson & Birkinshaw, 2004;Junni et al, 2013;Luo et al, 2018).…”
Section: Organizational Ambidexteritymentioning
confidence: 99%
“…In the balanced perspective, ambidexterity can be described as midpoint, or an optimal point on a continuum, with exploitation and exploration lying at the two ends. On the other hand, in the combined perspective, exploitation and exploration are considered independent activities, where their maximized level can produce a high degree of ambidexterity (Kassotaki, 2022;Fig. 1).…”
Section: Organizational Ambidexteritymentioning
confidence: 99%
“…This study contributes to the burgeoning research on ambidexterity in several ways. Firstly, it answers recent calls for enquiry into the micro-foundations and behavioural styles associated with ambidextrous leadership (Kafetzopoulos, 2022;Kassotaki, 2022;Tempelaar & Rosenkranz, 2019) and examines the unique and relative contribution of leaders' paradoxical thinking and integrator behaviours to their engagement with both exploration and exploitation behaviours. Secondly, our study extends the research on the influence of contextual contingencies on leader ambidexterity and tests for differences in ambidextrous behaviour along managerial levels and managerial roles.…”
Section: Introductionmentioning
confidence: 99%
“…While the advantages of ambidextrous leadership have been extolled in the literature (Jia et al, 2022), and leader attributes and behaviours such as response to paradoxes and leadership styles have been proposed as ambidexterity predictors, there is limited research that examines the unique and joint influence of these leader factors on ambidexterity (Kassotaki, 2022; Schnellbächer, Heidenreich, & Wald, 2019). Moreover, the associations between health-care leader responses to paradoxes, their leadership styles and ambidextrous behaviours has not been established.…”
Section: Introductionmentioning
confidence: 99%